Does inter-arm coordination change with distance in maximal and sub-maximal effort in freestyle swimming? - Schnitzler, C.; Ernwein, V.; Seifert, L.; Chollet, D. (First international symposium sciences and practices in swimming, 2006)
This study examined the changes during maximal 400-m freestyle swim trials in terms of spatio-temporal, physiological and subjective parameters. 12 national level competitors of both genders swam 400 m at maximal speed. They then swam 100, 200 and 300 m at the speed of the initial 400-m. Mean speed (V25) and index of coordination (IdC) were determined by video analysis every 25 m. Peak lactate value (Hlap) and subjective workload (TWL) were determined after each trial. Hlap and TWL increased significantly with distance swum. V25 showed significant Variation during the 400-m. However, IdC remained stable during the trial, despite inter-individual differences. Neither showed change when the distance was lowered. The TWL and Hlap values indicated that difficulty increased with race distance. IdC is thus not sensitive to the fatigue accumulated during maximal effort, and is not influenced by a controlled speed condition.